Nano-engineered hydrocolloid-based delivery systems for natural flavonoids: From structural diversity to bioavailability enhancement and therapeutic applications - Yueming Wang; Amin Zhang; Wenjie Chu; Chengliang Qi; Tianxing Zhou; Yu Pan; Yuhan Wang; Chengyang Wang; Yuan Liu; Wenli Wang (Food Hydrocolloids, 2027)

Global drivers and pathways of mariculture maturation, 1997–2022 - Guo Yu; Yueming Liu; Xiaomei Yang; Yonglong Lu; Vincent Lyne; Zhihua Wang (Aquaculture, 2027)

Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

Environmental regulation of sunken courtyards in standalone underground spaces: field measurements and ventilation-oriented design strategies - Yueming Wen; Meng Ouyang; Yitong Wang; Wenjie Peng; Chang Liu; Quan Jing; Yuchong Qian; Yuxuan Liu; Tongxin Guo; Hang Wei (Tunnelling and Underground Space Technology, 2026)

Cover crop-specific root-derived biopore structure is associated with biopore sheath bacterial facets in compacted soil columns - Peng Xiong; Guilong Li; Zejun Luo; Hao Li; Zhengfu Yue; Yueming Chen; Xiaolin He; Xiong Fang; Jia Liu; Jingjing Peng (Soil and Tillage Research, 2026)

Co-exposure to deoxynivalenol and hexavalent chromium is associated with intestinal injury, dysbiosis, and activation of ferroptosis and pyroptosis related pathways in broilers - Yueming Gu; Xinyuan Miao; Linrui Fan; Guodong Cai; Ruilong Song; Hui Zou; Jianhong Gu; Yan Yuan; Xuezhong Liu; Zongping Liu; Jianchun Bian (Food Research International, 2026)

Spatial confinement in zeolites dominates pentene monomolecular cracking pathway - Fang Li; Weiyong Zhong; Min Sun; Yiran Wang; Penghe Zhang; Yueming Liu; Mingyuan He (Chemical Engineering Journal, 2026)

Alpha-ketoglutaric acid alleviates litchi fruit browning and senescence via enhancing antioxidant capacity and energy homeostasis - Yuemin Yang; Rufang Deng; Mengting Liu; Xinguo Su; Yueming Jiang; Xuewu Duan; Guoxiang Jiang; Ting Li (Postharvest Biology and Technology, 2026)

Characterization of flavor compounds and core functional microorganisms during pile fermentation of Liupao tea - Yanjun Chen; Yuelan Pang; Yueming Liang; Zhusheng Liu; Zhonghua Liu; Qiming Hu; Fujing Pan (Food Chemistry, 2026)

A novel role for multifunctional NAC transcription factor SlNOR-like1: Enhancing flavonoid accumulation in tomato fruit exocarp by modulating glycosylation modification - Gangshuai Liu; Yueming Tang; Yiwen Yang; Jinghong Luo; Xiaodan Zhao; Daqi Fu; Jia Gao (Food Bioscience, 2026)

Piston ventilation modulates thermal comfort in subway hubs via a dual-path coupling mechanism: A field study in Nanjing, China - Yuxuan Liu; Jiawei Leng; Yueming Wen; Haifei Zhou; Deqing Lin; Yuchong Qian (Building and Environment, 2026)

Remote sensing and statistical data integration for spatial discrimination and mapping of mariculture products: A case study of Sansha Bay - Jie Jiang; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Dan Meng; Meiqi Zhou; Jialiang Liu (Ocean & Coastal Management, 2026)

Soybean integration increases pore connectivity and particulate organic matter while reducing shrinkage in saline Fluvo-aquic soil: An X-ray CT study - Tianyu Ding; Zichun Guo; Yueming Chen; Shenzhong Tian; Jianli Liu; Xinhua Peng (Soil and Tillage Research, 2026)

Mg/Fe-layered double hydroxide-loaded biochar enhances nitrogen retention and reduces geochemically reactive metal concentrations in paddy soil: Bacterial community responses - Hengxin Liu; Ruohan Li; Yueming Han; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

Invariant-feature segmentation unlocks robust large-area mapping of mariculture - Ziyu Jiang; Jinyan Xie; Jihao Peng; Huaqing Wu; Yue Liu; Cong Zeng; Yueming Liu; Xiaomei Yang; Ling Cao (Marine Environmental Research, 2026)

Differential effects of Cl- and SO42- anion systems on Ca2+-Mg2+-Mn2+ carbonate biomineralization induced by the halophilic Bacillus dokdonensis: Implications for Mn2+-containing saline wastewater treatment - Xueting Chen; Yueming Zhao; Hui Zhao; Memon Kashif Ali; Ran Shu; Bo Liu; Boyu Cai; Runxi Yin; Zuozhen Han; Huaxiao Yan (Journal of Hazardous Materials, 2026)

Towards low-carbon grain storage buildings: a systematic review of assessment methods and mitigation strategies - Ruoting Liu; Fei Yu; Meng Ouyang; Qi Zhao; Yueming Wen (Energy and Buildings, 2026)

Estimating downward shortwave radiation incorporating topographic effects using a hybrid physical and data-driven method: Algorithm development and long-term global product generation - Yichuan Ma; Tao He; Shunlin Liang; Xiaotong Zhang; Tim R. McVicar; Dejun Cai; Wanshan Peng; Yueming Zheng; Tong Liu; Xinyan Liu (Remote Sensing of Environment, 2026)

BrNAC046 involved in hydrogen peroxide-induced leaf senescence of postharvest Chinese flowering cabbage - Fengjun Li; Baoxiang Ren; Lilang Li; Xiangjin Kong; Hanzhi Liang; Hai Liu; Ling Wang; Yueming Jiang (Postharvest Biology and Technology, 2026)

Itaconate delays senescence and browning in litchi fruit via enhanced antioxidant capacity and energy metabolism - Mengling Qin; Jiaqi Xiao; Yueming Jiang; Xuewu Duan; Mengting Liu; Guoxiang Jiang (Postharvest Biology and Technology, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Epigenetic activation of lignin biosynthesis by CsJMJ16 confers enhanced resistance to Penicillium digitatum in citrus - Jing Zeng; Ting Li; Mengting Liu; Xiaoyan Duan; Jiechun Peng; Zhiwei Li; Guoxiang Jiang; Yueming Jiang; Xuewu Duan (Postharvest Biology and Technology, 2026)

Dynamic patterns of constraints, drivers and impacts of land-based aquaculture areas and their implications: A case of Guangdong, China from 1990 to 2020 - Ku Gao; Xiaomei Yang; Zhihua Wang; Yueming Liu; Feilin Lai; Junyao Zhang (Land Use Policy, 2026)

Waste eggshell-modified biochar for phosphorus recovery and its potential reuse as a sustainable fertilizer - Yixuan Feng; Yueming Chen; Xilin Guan; Zichao Zhao; Xinhao Gao; Xiaoning Liu; Shenzhong Tian (Journal of Environmental Chemical Engineering, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

In-situ constructed Ag/CNT hierarchical networks in TPU nanofibers for dual-mode triboelectric sensing - Shiqiang Ouyang; Feijie Wang; Yichi Liu; Suyang Wang; Yaoli Wang; Yuefan Liu; Zhixuan Mei; Kaixin Liao; Shenzhuo Zhang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Online monitoring of deposit-induced corrosion in a Waste-to-Energy boiler - Wenjie Liu; Yafang Wang; Yan Wang; Yongjun Liu; Anming Du; Qiongyu Ren; Xinran Zheng; Xiyu Chen; Minmin Zhou; Yueming Wang; Lunbo Duan (Waste Management, 2026)

Spatiotemporal heterogeneity of human footprint across China's coastal zone: Integrating geomorphic and policy drivers - Dan Meng; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Ku Gao (Ocean & Coastal Management, 2026)

Meclofenamic acid sodium inhibits litchi fruit senescence via integrated regulation of oxidative stress, energy metabolism, and m6A modification - Mengting Liu; Mengling Qin; Jiaqi Xiao; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Postharvest Biology and Technology, 2026)

Alpha-ketoglutarate alleviates chilling injury in banana fruit by promoting redox homeostasis and maintaining energy balance - Yuemin Yang; Rufang Deng; Yueming Jiang; Xuewu Duan; Zhengke Zhang; Guoxiang Jiang; Mengting Liu (Postharvest Biology and Technology, 2026)

Arbuscular mycorrhizal symbiosis enhances microbial contribution to mineral-associated organic carbon persistence in soil: Insights from soil microbial community and microbial necromass carbon - Yin LIU; Jin QIAN; Yueming ZHU; Jing HU; Bianhe LU; Yuxuan HE; Junwei SHEN (Pedosphere, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

A Remote Sensing Monitoring System for Marine Red Tides Based on Targeted Negative Sample Selection Strategies - Qichen Fan; Yong Liu; Yueming Liu; Xiaomei Yang; Zhihua Wang (Journal of Marine Science and Engineering, 2026)
The monitoring of harmful algal blooms (HABs) constitutes a vital component of marine environmental protection and the sustainable development of the marine economy. However, the highly dynamic nature of these small targets, compounded by the complex water color interference prevalent in the coastal waters where HABs frequently occur, has resulted in traditional remote sensing monitoring methods, particularly those relying on fixed spectral index thresholds and pixel-wise binarization, suffering from imprecise identification in turbid coastal waters where suspended sediments, cloud cover, and sun glint create spectral confusion. These methods also exhibit low automation due to manual threshold adjustment requirements and poor transferability across different spatiotemporal conditions. Consequently, these methods struggle to meet practical application requirements. This study establishes a U-net model-based remote sensing identification framework for red tides using HY-1D CZI imagery (50 m resolution, 1–3 day revisit), targeted negative sample strategies, and event-level accuracy validation methods to achieve efficient marine red tide detection. Targeted negative sample selection involves purposefully selecting spectrally ambiguous regions as negative samples, aiming to enhance recognition accuracy and sample selection efficiency. The combination of targeted sampling with deep learning enables portability to new spatiotemporal contexts by learning invariant spectral–spatial features rather than relying on scene-specific thresholds. Experimental results demonstrate that the targeted negative sample strategy reduces event-level model false negatives by 27%, false positives by 36%, and increases the F1 score by 0.3217. Using an identical sample size, the targeted sample selection strategy yields an F1 score 0.0479 higher than random sampling. To achieve equivalent recognition accuracy, an increased number of random samples would be required. Comparative experiments reveal that the proposed method enhances sample selection efficiency by 87.5%. Transferability is demonstrated through successful identification of red tide patches in Wenzhou waters on 13 April 2022, without model retraining. This demonstrates that red tide remote sensing recognition based on targeted sample selection enables efficient, precise, and automated identification without human intervention, providing a reliable technical solution for operational marine red tide monitoring.

Distinct mowing effects on organic carbon storage and dynamics in Spartina alterniflora and Phragmites australis sediments - Yueming Wu; Danqing Sun; Shan Jiang; Beiyun Xu; Jing Liu; Jian Li; Yiyun Wang; Ying Wu (Ocean & Coastal Management, 2026)

Corrigendum to “Insight on the interaction between chickpea protein isolate and dextran: Structural analysis, functional characterization and co-encapsulated W/O/W emulsion formation” [Food Res. Int. 213 (2025) 116593] - Jing Zhang; Yan Shi; Yueming Hu; Wei Fan; Wei Liu; Yipu Liu (Food Research International, 2026)

Does algal trophic mode affect the removal of norfloxacin? Insights from Tetradesmus obliquus - Musheng Ji; Jin Qian; Xiaxia Li; Yueming Zhu; Yin Liu; Bianhe Lu; Sijing Tang; Junwei Shen; Yuhang Zong (Journal of Hazardous Materials, 2026)

The combined exposure to antibiotics intensified the phytotoxicity of perovskite composite nanoparticles to Phragmites communis - Yuxuan He; Yueming Zhu; Jin Qian; Bianhe Lu; Sijing Tang; Yin Liu; Junwei Shen; Musheng Ji (Journal of Environmental Management, 2026)

Electrochemical insights into the High-Temperature corrosion mechanism of 12Cr1MoV steel under Chlorine-Rich conditions - Yafang Wang; Wenjie Liu; Minmin Zhou; Wenxiu Yang; Dongfu Wang; Yueming Wang; Lunbo Duan (Fuel, 2026)

Effect of strong reducing atmosphere on mineral transformation in high-iron and high-calcium coal during plasma underground coal gasification - Chuan Qi; Weibin Wang; Jiahong Cao; Xiongchao Lin; Yueming Liu; Shuqin Liu (Fuel, 2026)

Application of riboflavin delays the browning of harvested litchi during storage at room temperature - Jiechun Peng; Ting Li; Mengting Liu; Jiangtao Zhang; Xiaoyan Duan; Ying Li; Hanzhi Liang; Pedro Garcia-Caparros; Yueming Jiang; Xuewu Duan (Food Control, 2026)

Bromide-containing surfactants enabling singlet oxygen-dominated non-radical oxidation process for efficient degradation of aromatic pollutants in soil and groundwater - Yueming Han; Zhuolun Li; Guanqing Chen; Hengxin Liu; Shichao Feng; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

Arachidin-2 suppresses Peronophythora litchii and postharvest decay of litchi fruit - Bailin Li; Xueying Meng; Fen Liu; Bao Yang; Sui Kiat Chang; Yueming Jiang (Food Chemistry, 2026)

Contrasting soil structure and yield responses to 8-year conservation tillage in Fluvo-aquic and Shajiang black soils - Tianyu Ding; Zichun Guo; Yueming Chen; Zizhou Yu; Shenzhong Tian; Jianli Liu; Xinhua Peng (European Journal of Agronomy, 2026)

Corrigendum to “Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit” [Postharvest Biol. Technol. 224 (2025) 113466] - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

Alveolar macrophages polarization switch via α2-adrenoceptor activation ameliorates pulmonary inflammation following kidney ischemia reperfusion - Jieyu Li; Zhigang Qin; Xinhai He; Ling Jiang; Xiangfeng Liu; Zhengwei Xue; Xiao Li; Yueming Xu; Peng Li; Jianteng Gu (Inflammation Research, 2025)

Pore structure modulation and surface functionalization boosted adsorption of PFAS on porous carbon: Experimental and theoretical investigations - Bei Zhang; Daiki Moriyama; Thilini Maheshika Herath; Huan Zhao; Yuqiao Bai; Yueming Dang; Wei Liu; Hiromichi Kato; Koichi Yamamoto; Yasuhide Mochizuki; Naoki Arimitsu; Akira Nakajima; et al. (Journal of Hazardous Materials, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Bioinspired graphene-based aerogel polyurethane multifunctional coatings with high-temperature resistance, anti-corrosion and anti-fouling properties - Yuping Liu; Limei Tian; Jie Zhao; Jiarun Tian; Yueming Wang; Jiyu Sun (Chemical Engineering Journal, 2025)

Enhancing the output of cellulose-based triboelectric nanogenerators via dual interfacial polarization effects - Feijie Wang; Suyang Wang; Hao Wang; Yichi Liu; Shiqiang Ouyang; Shenzhuo Zhang; Yueming Hu; Junhua Zhao; Shufeng Ma; Zhen Wu; Liqiang Wang (Carbohydrate Polymers, 2025)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

Investigation of the mechanism of H2O2 combined pulsed electric field treatment reducing the antigenicity of parvalbumin and tropomyosin by high-resolution mass spectrometry, molecular dynamics and DFT computation - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Jie Cheng; Haibin Liu; Yueming Hu; Zongcai Tu (Innovative Food Science & Emerging Technologies, 2025)

Chelation of cerium (III) with fish skin collagen peptides: Improving the in vitro stability and bioavailability of inorganic cerium - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu; Jie Cheng; Hai-bin Liu; Pingwei Wen (Food Research International, 2025)

The role of amino acids in delaying the pulp breakdown of litchi fruit during postharvest storage - Lei Wei; Ziming You; Ping Liu; Hong Zhu; Xuewu Duan; Yueming Jiang; Ze Yun (Food Chemistry, 2025)

MOFs-derived FeNi bimetallic phosphide with tightly coupled heterogeneous interface for PMS activation - Xiaoyang Liu; Yueming Zhu; Minghui He; Chenyu Zhang; Gancheng Zuo; Yuting Wang; Shaogui Yang; Huan He (Chemical Engineering Journal, 2025)

ALN-modified MnO2-x/PEEK implant for bone-targeted catalytic therapy in postoperative osteosarcoma repair - Miaomiao He; Ce Zhu; Dan Sun; Yueming Song; Ganjun Feng; Limin Liu; Li Zhang (Chemical Engineering Journal, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

Simulated Study of a Multi-stage Permeable Reactive Barrier for In-Situ AMD Treatment of a Closed High-Sulfur Coal Mine - Yueming Qi; Pei Zhou; Dan Jiang; Lai Zhou; Yanzhuo Liu; Jiehui Zhang (Mine Water and the Environment, 2025)

Insight on the interaction between chickpea protein isolate and dextran: Structural analysis, functional characterization and co-encapsulated W/O/W emulsion formation - Jing Zhang; Yan Shi; Yueming Hu; Wei Fan; Wei Liu; Yipu Liu (Food Research International, 2025)

Overcoming the Diagnostic Challenges in Cutaneous Cryptococcosis Caused by Cryptococcus neoformans: A Case Study Utilizing Metagenomic Next-Generation Sequencing - Liujun Lu; Yulin Chen; Minfang Leng; Shuquan He; Qunlan Liu; Songyun Zou; Yueming Liu; Feixiang Fan (Mycopathologia, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Polystyrene nanoplastics reshape the peatland plants (Sphagnum) bacteriome under simulated wet-deposition pathway: Insights into unequal impact of ecological niches - Sijing Tang; Jin Qian; Yueming Zhu; Bianhe Lu; Yuxuan He; Yin Liu; Kailin Xu; Junwei Shen (Journal of Hazardous Materials, 2025)

Jasmonate activates PuMYC2 and decreases histone acetylation levels to inhibit the ester aroma catabolism in cold-stored Nanguo pears fruit - Liyong Qi; Nannan Zang; Juntong Jin; Weiting Liu; Xiaojing Li; Yueming Yang; Baofeng Wang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2025)

Tyr-Asp treatment delays senescence in litchi fruit by enhancing redox balance and maintaining energy homeostasis - Ruan Zhiyan; Yanxuan Zhu; Mengting Liu; Yijie Zhou; Xinguo Su; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Construction of W/O/W microcapsules based on the combination of polyglycerol polyricinoleate/protein for the co-encapsulation of crocin and quercetin: Physical properties, stability and in vitro digestion - Wei Fan; Yan Shi; Yueming Hu; Shu Wang; Jing Zhang; Wei Liu (Food Chemistry, 2025)

Transient Power Stabilization in Marine Microgrids: Improved Droop Control and Feedforward Strategies for Heterogeneous Gas Turbines with Hybrid Energy Storage - Zemin Ding; Yueming Li; Yongbao Liu; Youhong Yu (Journal of Marine Science and Engineering, 2025)
To address the complexity of power allocation in parallel operation systems combining single-shaft and split-shaft gas turbine generators, this paper proposes a coordinated power allocation strategy based on enhanced voltage droop control for marine power systems integrated with hybrid energy storage comprising flywheel and battery subsystems. Furthermore, to mitigate significant power sharing deviations during transient/pulsed load conditions in shipboard application, a feedforward compensation strategy is developed. Simulation results demonstrate that the improved droop control maintains power sharing deviations below 3.5% across steady-state operations and gradual load variations, ensuring system stability and balanced power distribution. However, abrupt load changes induce over 20% deviations, compromising parallel operation reliability. The proposed feedforward compensation strategy effectively restricts deviations within 4% under specified transient and pulsed load scenarios, satisfying both parallel operation criteria and grid power quality requirements. Validation is performed on a parallel system comprising two distinct gas turbine configurations.

Transcription factor AcAGL9 and AcBEH1 synergistically regulate carotenoid biosynthesis during pineapple fruit ripening - Mengting Liu; Ting Li; Rufang Deng; Zhengke Zhang; Yijie Zhou; Xuewu Duan; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Evaluation of factors influencing full wave equation depth migration - Anyu Li; Yueming Ye; Xiangyu Zhu; Tao Liu; Huimin Zhang; Yong Xia (Journal of Applied Geophysics, 2025)

Effects of storage durations on flavour and bacterial communities in Liupao tea - Yueming Liang; Zhusheng Liu; Yuelan Pang; Min Li; Shengmeng Zheng; Fujing Pan; Chunyu Guo; Qianhua Wu; Ting Chen; Qiang Li; Zhonghua Liu (Food Chemistry, 2025)

Spatial extraction of sea-cucumber aquaculture ponds using remote sensing spectral and temporal features - Ruoqi Du; He Li; Chong Huang; Qingsheng Liu; Yueming Liu; Zhihua Wang (Frontiers in Marine Science, 2025)
The spatial distribution of aquaculture ponds plays a critical role in the layout, management, and evaluation of the aquaculture industry. While extensive research has been conducted on aquaculture pond extraction and monitoring, studies focusing on the differentiation of aquaculture ponds by species remain limited. The similar shapes and spectral features of water bodies associated with different species pose a challenge for extraction. A method for extracting sea-cucumber aquaculture ponds is proposed based on spectral temporal features using Sentinel-2 satellite imagery in this study. The method involves selecting the optimal sensitive spectral bands or combinations to construct two remote sensing indices of land-based aquaculture ponds. Using a time-series dataset of these indices, three key features—the mean and two slopes—are extracted. The corresponding time windows and thresholds for these key features are identified to develop a decision-tree algorithm for extracting sea-cucumber ponds. This method was applied to coastal aquaculture zones in Liaoning Province, China, to identify the spatial distribution of sea-cucumber aquaculture ponds in 2016 and 2023. The results showed that: (1) the proposed method achieved high extraction accuracy, with an overall accuracy of 79.24%; (2) Total area of sea-cucumber ponds in Liaoning Province was 931.08 km 2 , primarily located along the Huludao Xingcheng-Jinzhou Linghai and Yingkou Xishi-Dalian Zhuanghe coastal zones; (3) Over the past seven years, the area of sea-cucumber ponds increased by 624.57 km 2 , with expansion concentrated on the northwest coast of Liaodong Bay and both the eastern and western sides of the Liaodong Peninsula. These findings provide scientific support for the sustainable development of sea-cucumber aquaculture.

New insights of flavonoid glycosidases and their application in food industry - Yingjun Liu; Qiuxia Yang; Yushan Guo; Yueming Jiang; Hong Zhu; Bao Yang (Critical Reviews in Food Science and Nutrition, 2025)

Arabinogalacturonan in functional food “Astragalus membranaceus root”: Structure and immunomodulatory activity - Zhili Sheng; Hui Liu; Bailin Li; Hong Zhu; Yueming Jiang; Bao Yang (Food Hydrocolloids, 2025)

Interaction of Ca2+ and Fe3+ in co-precipitation process induced by Virgibacillus dokdonensis and its application - Huaxiao Yan; Yuping Liu; Haojuan Zhang; Shengping Jin; Zuozhen Han; Jusun Woo; Maurice E. Tucker; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Yueming Zhao; et al. (Journal of Environmental Sciences, 2025)

Interaction between root exudates and PFOS mobility: Effects on rhizosphere microbial health in wetland ecosystems - Bianhe Lu; Peifang Wang; Yueming Zhu; Jing Hu; Jin Qian; Yuanyuan Huang; Junwei Shen; Sijing Tang; Yin Liu (Environmental Pollution, 2025)

High-performance flexible organic field-effect transistor based on highly ordered poly(3-hexylthiophene) nanowires - Liangkun Lu; Meng Si; Shaobo Jin; Zirui Zhao; Xuling Liu; Liguo Dai; Yueming Zhou; Hongjie Yang; Guoyong Ye (Chemical Engineering Journal, 2025)

Association between exposure to arsenic, cadmium, and lead and chronic kidney disease: evidence from four practical statistical models - Jiongli Huang; Jingying Mao; Huilin Liu; Zhongyou Li; Guiyun Liang; Dabiao Zhang; Junchao Yang; Wen Qin; Pingjing Wen; Yueming Jiang; Zhaoyu Mo (Environmental Geochemistry and Health, 2025)

Disentangling the effects of meteorology and emissions from anthropogenic and biogenic sources on the increased surface ozone in Eastern China - Min Shao; Shun Lv; Yueming Song; Rui Liu; Qili Dai (Atmospheric Research, 2024)

Integrating aboveground and underground environments to enhance underground natural ventilation in the tropics: Case studies in Singapore - Yueming Wen; Siu-Kit Lau; Ke Liu; Zhixin Xu; Jiawei Leng (Tunnelling and Underground Space Technology, 2024)

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

Acid strength controlled reaction pathways of propylene conversion under olefin cracking conditions over ZSM-5 - Qin Zhao; Fang Li; Yiran Wang; Yueming Liu; Mingyuan He (Fuel, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Sodium selenite enhances the production of functional proteins and biomass in Chlorella pyrenoidosa 038F by promoting acetate assimilation under heterotrophic cultivation - Jingjing Shangguan; Na Yang; Litao Zhang; Jianguo Liu; Yueming Li; Jianchun Xu; Xiuluan Xia; Bingzheng Xu (Aquaculture, 2024)

Co-removal and recycling of Ba2+ and Ca2+ in hypersaline wastewater based on the microbially induced carbonate precipitation technique: Overlooked Ba2+ in extracellular and intracellular vaterite - Huaxiao Yan; Xiaofei Zhu; Zhiyong Liu; Shengping Jin; Jilai Liu; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Maurice E. Tucker; et al. (Journal of Hazardous Materials, 2024)

Motion Analysis of International Energy Agency Wind 15 MW Floating Offshore Wind Turbine under Extreme Conditions - Zengliang Chang; Yueming Zheng; Meng Qu; Xingguo Gao; Xiaojie Tian; Guijie Liu (Journal of Marine Science and Engineering, 2024)
In recent years, ultra-large-scale offshore wind turbines have attracted widespread attention. However, accurately evaluating the motion responses of offshore wind turbines under extreme conditions, especially for semisubmersible floating off-shore wind turbines, is often challenging. In order to assess the operational behavior of wind turbines under wind and wave loads, this paper adopted a numerical analysis method to solve the motion responses under extreme conditions. It specifically examines the motion responses of the IEA 15 MW wind turbine in terms of surge, heave, and pitch direction, focusing on environmental loads that occur once every 50 years. The results show that the wind turbine can still operate normally under the Ultimate condition. However, the average amplitude increased by 7% in the pitch direction and decreased by 4% in the heave direction compared to the rated condition. Under extreme conditions (occurring once every 50 years), with the wind turbine parked, the average amplitude in the surge direction reduced by 33%, while the average amplitude in the pitch direction reduced by 106%. Thus, it is essential to pitch the blades and brake the generator in extreme environmental conditions to ensure the safety of the wind turbine.

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

Immobilization of a novel d-allulose 3-epimerase from Bacillus cihuensis within metal-organic frameworks - Ziyi Li; Tao Liu; Wenwen Pei; Yan Zeng; Yan Men; Xuegang Luo; Yueming Zhu; Yuanxia Sun (Food Bioscience, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

Effects of Detritus Treatments on Soil Microbial Community Composition, Structure and Nutrient Limitation in a Subtropical Karst Ecosystem - Peiwen Liu; Suya Ding; Ning Liu; Yanhua Mo; Yueming Liang; Jiangming Ma (Journal of Soil Science and Plant Nutrition, 2024)

A new curve of critical leaf nitrogen concentration based on the maximum root dry matter for diagnosing nitrogen nutritional status of sweetpotato - Zhi Zhang; Ximing Xu; Minghuan Jin; Jiacheng Bai; Xing Shu; Lijuan Deng; Siyu Wang; Yueming Zhu; Yuheng Liu; Guoquan Lu; Zunfu Lv (European Journal of Agronomy, 2024)

Structural insight into the dual-antagonistic mechanism of AB928 on adenosine A2 receptors - Yuan Weng; Xinyu Yang; Qiansen Zhang; Ying Chen; Yueming Xu; Chenyu Zhu; Qiong Xie; Yonghui Wang; Huaiyu Yang; Mingyao Liu; Weiqiang Lu; Gaojie Song (Science China Life Sciences, 2024)

Evaluation of coastal zone development and utilization considering natural ontology, a case study in Liaoning Province, China - Guo Yu; Zhihua Wang; Yueming Liu; Xiaomei Yang; Junyao Zhang; Ku Gao (Ocean & Coastal Management, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Insight into the molecular mechanism underlying the enhancement of antioxidant activity in ovalbumin by high-energy electron beam irradiation - Haiqi Chen; Zhongyue Bian; Pingwei Wen; Hui Wang; Yueming Hu; Zongcai Tu; Guangxian Liu (Food Chemistry, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

Water quality and microecosystem of water tanks in karst mountainous area, Southwest China - Qigang Wang; Guanghui Jiang; Ziyong Sun; Yueming Liang; Fan Liu; Jie Shi (Environmental Science and Pollution Research, 2024)

Identification and stability evaluation of polyphenol oxidase substrates of pineapple fruit - Hai Liu; Jiangming Li; Yueming Jiang; Fengjun Li (Food Chemistry, 2024)

Hexaconazole and binary mixtures of it plus fludioxonil efficiently control tomato leaf mold caused by Cladosporium fulvum - Shuai Hu; Xiuhuan Li; Lele Chen; Yueming Wu; Lingtao Meng; Kai Wang; Beixing Li; Feng Liu (Crop Protection, 2023)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Changes in the spatial distribution of mariculture in China over the past 20 years - Yueming Liu; Zhihua Wang; Xiaomei Yang; Shaoqiang Wang; Xiaoliang Liu; Bin Liu; Junyao Zhang; Dan Meng; Kaimeng Ding; Ku Gao; Xiaowei Zeng; Yaxin Ding (Journal of Geographical Sciences, 2023)

Increased aerosol scattering contributes to the recent monsoon rainfall decrease over the Gangetic Plain - Tong Ying; Jing Li; Zhongjing Jiang; Guanyu Liu; Zhenyu Zhang; Lu Zhang; Yueming Dong; Chuanfeng Zhao (Science Bulletin, 2023)

Research on the hydrodynamic performance of AUVs in small size open channel area - Jian Cao; Yaoqi Feng; Yueming Li; Hongwei Li; Chao Han; Yushan Sun; Zhaohang Liu (Ocean Engineering, 2023)

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

Comparison of ovalbumin glycation induced by high-temperature steaming and high-temperature baking: A study combining conventional spectroscopy with high-resolution mass spectrometry - Yueming Hu; Haiqi Chen; Yifan Yang; Siqiong Zhang; Zuohua Xie; Jiaojiao Liu; Qiannan Jiang; Jun Liu; Pingwei Wen (Food Research International, 2023)

Changes in dilution curves of critical nitrogen concentration in sweetpotato under different potassium conditions - Lijuan Deng; Ximing Xu; Yueming Zhu; Weichen He; Minghuan Jin; Yuheng Liu; Guoquan Lu; Zunfu Lv (Field Crops Research, 2023)

New insights of fig (Ficus carica L.) as a potential function food - Qiuxia Yang; Yingjun Liu; Yushan Guo; Yueming Jiang; Lingrong Wen; Bao Yang (Trends in Food Science & Technology, 2023)

Underwater object tracker: UOSTrack for marine organism grasping of underwater vehicles - Yunfeng Li; Bo Wang; Ye Li; Zhuoyan Liu; Wei Huo; Yueming Li; Jian Cao (Ocean Engineering, 2023)

Revealing the crystal phase effect of CeO2 in spinel-based nanocatalysts toward the peroxymonosulfate activation for organics degradation - Yuxuan He; Yueming Zhu; Jin Qian; Peifang Wang; Yuhang Zhang; Kailin Xu; Bianhe Lu; Yin Liu; Junwei Shen (Chemical Engineering Journal, 2023)

Relationship between summer time near-surface ozone concentration and planetary boundary layer height in Beijing - Chongzhao Zhang; Zhongjing Jiang; Meijing Liu; Yueming Dong; Jing Li (Atmospheric Research, 2023)

Characterization of nongxiang- and soy sauce-type distilled grains and their application in enhancing polyunsaturated fatty acid and triacylglyceride production from Chlorella sp. 038F - Na Yang; Jingjing Shangguan; Litao Zhang; Yueming Li; Jianchun Xu; Xiuluan Xia; Jianguo Liu (Journal of Environmental Chemical Engineering, 2023)

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

Theoretical Study on Rock-Electric Characteristics of Complex Shaly Sandstones and its Application to Reservoir Saturation Evaluation - He Meng; Yueming Ye; Tangyan Liu; Shiqiong Liu; Cun Yang; Libao Wang (Natural Resources Research, 2023)

Sustainable underground environment integrating hybrid ventilation, photovoltaic thermal and ground source heat pump - Yueming Wen; Siu-Kit Lau; Jiawei Leng; Ke Liu (Sustainable Cities and Society, 2023)

High-ratio {100} plane-exposed ZnO nanosheets with dual-active centers for simultaneous photocatalytic Cr(VI) reduction and Cr(III) adsorption from water - Xiao Li; Jiajia Liu; Jing Feng; Tong Wei; Zhongxiang Zhou; Jun Ma; Yueming Ren; Yanqing Shen (Journal of Hazardous Materials, 2023)

Flavor substances of low-valued red swamp crayfish (Procambarus clarkii) hydrolysates derived from double enzymatic systems - Chujun Li; Zongcai Tu; Wenyu Liu; Chunlin Wu; Yueming Hu; Hui Wang (Food Research International, 2023)

Nitric oxide is involved in melatonin-induced cold tolerance in postharvest litchi fruit - Jialiang Liu; Wanli Zhang; Meijiao Hu; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Guoxiang Jiang (Postharvest Biology and Technology, 2023)

Decreasing Vulnerability of Storm Surge Disasters in Coastal Cities of China over the Past 30 Years - Dan Meng; Yueming Liu; Zhihua Wang; Xiaomei Yang; Xiaoliang Liu; Junyao Zhang; Ku Gao (Journal of Marine Science and Engineering, 2023)
From 2000 to 2020, storm surges occurred 397 times in China, resulting in direct economic losses of up to CNY 220.64 billion. Storm surges not only threaten safety but also cause property damage; hence, it is necessary to assess the changes in vulnerability to storm surges in order to understand how to reduce said vulnerability. Fifteen coastal cities of four types were chosen, with different levels of urban development, rapid expansion of impervious surface, high extent of agricultural land, and high fishery output value. Viewing vulnerability through the dimensions of exposure, sensitivity, and adaptability, a GIS and RS were used to evaluate and assess the vulnerability in 15 coastal cities in China over the past 30 years. The results indicated that the vulnerability of these 15 Chinese cities presented the characteristics of a continuous downward trend from 1990 to 2020, and the average rate of reduction in vulnerability over the 10 years from 2005 to 2015 was the highest, at 2.23%. The areas of high vulnerability shifted from the southern region to the northern region. The vulnerabilities in the southern region, with Shanghai, Shenzhen, and Dongguan, changed significantly, to 3.30%, 3.20%, and 3.45%, respectively. An important factor in determining vulnerability reductions is a city’s ability to adapt to storm surges. Coastal cities can improve their adaptability to storm surge disasters through general public budget expenditure, investment in fixed assets, GDP, and medical and health services, thereby alleviating their vulnerability. Due to China’s frequent storm surge disasters during the 2005–2015 period, government departments have strengthened the investment of relevant resources in adaptive indicators, ultimately causing the cities’ vulnerability to rapidly decrease during this period.

Co-60 gamma irradiation induced ovalbumin-glucose glycation and allergenicity reduction revealed by high-resolution mass spectrometry and ELISA assay - Guang-xian Liu; Zong-cai Tu; Hui Wang; Yueming Hu; Wen-hua Yang (Food Chemistry, 2023)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

Simulation and risk assessment of typical antibiotics in the multi-media environment of the Yangtze River Estuary under tidal effect - Chaomeng Dai; Yueming Han; Yan Li; Yanping Duan; Shuguang Liu; Yalei Zhang; Yaojen Tu (Environmental Science and Pollution Research, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Safety and efficacy of new oral anticoagulants compared to those of warfarin in AF patients with cancer: a meta-analysis of randomized clinical trials and observational studies - Yueming Chen; Min Mao; Jing Chang; Jing Yan; Tiantian Yang; Yang Liu; Meng Luo; Yuhao Hu; Qi Yang; Lin Zhou; Kanghua Ma (European Journal of Clinical Pharmacology, 2021)

Representativeness and Redundancy-Based Band Selection for Hyperspectral Image Classification` - Yufei Liu; Xiaorun Li; Yueming Feng; Liaoying Zhao; Wenqiang Zhang (International Journal of Remote Sensing, 2021)

Study on calculation and validation of tropospheric ozone by ozone monitoring instrument – microwave limb sounder over China - Yueming Hu; Huanhuan Yan; Xingying Zhang; Yi Gao; Xiangdong Zheng; Xuyan Liu (International Journal of Remote Sensing, 2020)

Effect of aluminate content in cement on the long-term sulfate resistance of cement stabilized sand - Kaiwei Liu; Yueming Wang; Ning-Jun Jiang; Aiguo Wang; Daosheng Sun; Xingxing Chen (Marine Georesources & Geotechnology, 2020)

Research on a novel extraction method using Deep Learning based on GF-2 images for aquaculture areas - Bo Cheng; Chenbin Liang; Xunan Liu; Yueming Liu; Xiaoxiao Ma; Guizhou Wang (International Journal of Remote Sensing, 2020)

Aquaculture area extraction and vulnerability assessment in Sanduao based on richer convolutional features network model - Yueming Liu; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Fengshuo Yang (Journal of Oceanology and Limnology, 2019)

Object-based classification of cloudy coastal areas using medium-resolution optical and SAR images for vulnerability assessment of marine disaster - Fengshuo Yang; Xiaomei Yang; Zhihua Wang; Chen Lu; Zhi Li; Yueming Liu (Journal of Oceanology and Limnology, 2019)

Increased associated effects of topography and litter and soil nutrients on soil enzyme activities and microbial biomass along vegetation successions in karst ecosystem, southwestern China - Fujing Pan; Wei Zhang; Yueming Liang; Shujuan Liu; Kelin Wang (Environmental Science and Pollution Research, 2018)

Estimation of net primary productivity of forests by modified CASA models and remotely sensed data - Zhenhua Liu; Manqin Hu; Yueming Hu; Guangxing Wang (International Journal of Remote Sensing, 2018)

Treatment of cauda equina syndrome caused by lumbar disc herniation with percutaneous endoscopic lumbar discectomy - Xiaolong Li; Qingyu Dou; Shuai Hu; Jiaxiang Liu; Qingquan Kong; Jiancheng Zeng; Yueming Song (Acta Neurologica Belgica, 2016)

Molecular cloning and potential function prediction of homologous SOC1 genes in tree peony - Shunli Wang; Margherita Beruto; Jingqi Xue; Fuyong Zhu; Chuanjiao Liu; Yueming Yan; Xiuxin Zhang (Plant Cell Reports, 2015)

EOLA1 protects lipopolysaccharide induced IL-6 production and apoptosis by regulation of MT2A in human umbilical vein endothelial cells - Yueming Liu; Hairong Liu; Wenhai Chen; Ting Yang; Wei Zhang (Molecular and Cellular Biochemistry, 2014)

Diagnosing Climate Change and Hydrological Responses in the Past Decades for a Minimally-disturbed Headwater Basin in South China - Yiping Wu; Dongsheng Cheng; Wende Yan; Shuguang Liu; Wenhua Xiang; Ji Chen; Yueming Hu; Qian Wu (Water Resources Management, 2014)

Integrating fuzzy logic with piecewise linear regression for detecting vegetation greenness change in the Yukon River Basin, Alaska - Yueju Xue; Shuguang Liu; Li Zhang; Yueming Hu (International Journal of Remote Sensing, 2013)

Identification and characterization of a novel l-arabinose isomerase from Anoxybacillus flavithermus useful in d-tagatose production - Yanjun Li; Yueming Zhu; Anjun Liu; Yuanxia Sun (Extremophiles, 2011)

KLF6 inhibits estrogen receptor-mediated cell growth in breast cancer via a c-Src-mediated pathway - Jun Liu; Tian Du; Yufeng Yuan; YueMing He; Zui Tan; Zhisu Liu (Molecular and Cellular Biochemistry, 2010)

Beamlet prestack depth migration and illumination: A test based on the Marmousi model - Yueming Ye; Zhenchun Li; Wengong Han; Qingmin Liu (Applied Geophysics, 2006)

Experimental study on full-scale steel beam-to-column moment connections - Jiaru Qian; Haiqun Yu; Feng Yan; Hai Dong; Jianhua Li; Yueming Liu (Earthquake Engineering and Engineering Vibration, 2005)

Capillary zone electrophoresis analysis of gliadin proteins from Chinese and Yugoslav winter wheat cultivars - Yueming Yan; Gordana Surlan-Momirovic; Slaven Prodanovic; Dragica Zoric; Guangtian Liu (Euphytica, 1999)